Thermotropic lateral translational motion of intramembrane particles in the inner mitochondrial membrane and its inhibition by artificial peripheral proteins (The Rockefeller University Press, 1977)
Freeze fracturing and deep etching have been used to study thermotropic lateral translational motion of intramembrane particles and membrane surface anionic groups in the inner mitochondrial membrane. When the inner membrane is equilibrated at low temperature, the fracture faces of both halves of the membrane reveal a lateral separation between intramembrane particles and particle free, large smooth patches. Such separation is completely reversed through free lateral translational diffusion by reversing the temperature. The low temperature induced, particle-free, smooth membrane patches appear to represent regions of protein-excluding, ordered bilayer lipid which form during thermotropic liquid crystalline to gel state phase transitions. When polycationic ferritin is electrostatically bound to anionic groups exposed at the membrane surface at concentrations which inhibit the activities of cytochrome c oxidase and succinate permease, the bound ferritin migrates with intramembrane particles during the thermotropic lateral separation between the membrane particles and smooth patches. When bound polycationic ferritin is cross-bridged with native ferritin, an artificial peripheral protein lattice forms in association with the surface anionic groups and diminishes the thermotropic lateral translational motion of intramembrane particles in the membrane. These results reveal that the anionic groups of metabolically active integral proteins which are known to be exposed at the surface of the inner mitochondrial membrane migrate with intramembrane particles in the plane of the membrane under conditions which induce lipid-protein lateral separations. In addition, cross-bridging of the anionic groups through an artificial peripheral protein lattice appears to diminish such induced lipid protein lateral separations.